2017
DOI: 10.1007/s00168-017-0822-9
|View full text |Cite
|
Sign up to set email alerts
|

Regional economic resilience: the experience of the Italian local labor systems

Abstract: After defining the concept of resilience and its application to the regional context, the paper presents a preliminary evaluation of regional economic resilience in the case of the Italian regions. In doing so, we follow the approach by Martin (J Econ Geogr 12:1–32, 2012) and Martin and Sunley (2015) who identify three different dimensions to regional economic resilience: (a) resistance, i.e., the degree of sensitivity or depth of reaction of a regional economy to a recessionary shock; (b) recovery, i.e., the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
154
1
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(178 citation statements)
references
References 27 publications
10
154
1
13
Order By: Relevance
“…This shows that municipalities linked to agriculture have been probably more sheltered from the global economic crisis. Similar results have been found in Faggian, Gemmiti, Jaquet, and Santini (2018) in the case of Italian regions who explain this positive relation to resilience by the fact that food is a very inelastic good. 11 Regarding the diversity of the local economic structure, the results show that greater diversity of employment-as reflected by the negative coefficient for the Herfindahl 10 Martin and Sunley (2015) highlight, for example, financial and governance arrangements as important determinants of regional economic resilience together with the industrial and business structure and labour market conditions.…”
Section: Local Industrial Structuresupporting
confidence: 87%
“…This shows that municipalities linked to agriculture have been probably more sheltered from the global economic crisis. Similar results have been found in Faggian, Gemmiti, Jaquet, and Santini (2018) in the case of Italian regions who explain this positive relation to resilience by the fact that food is a very inelastic good. 11 Regarding the diversity of the local economic structure, the results show that greater diversity of employment-as reflected by the negative coefficient for the Herfindahl 10 Martin and Sunley (2015) highlight, for example, financial and governance arrangements as important determinants of regional economic resilience together with the industrial and business structure and labour market conditions.…”
Section: Local Industrial Structuresupporting
confidence: 87%
“…Empirical research on short‐term shock often focused on these two components and found some interesting results. Pudelko, Hundt, and Holtermann () found a possible negative relationship between regional resistance and recovery in German regions during the Great Recession of 2008/2009, while Faggian et al () found that there is no significant correlation between resistance and recovery in Italy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The relationship between resistance and recoverability was a controversial issue and caused some debate. Faggian et al () found that there was no significant correlation between resistance and recovery; Martin, Sunley, Gardiner, and Tyler () found that there has been a positive relationship between resistance and recoverability across regions in UK; while Tan et al () found that they had a strong negative correlation in Northeast China. In short, economic resilience in terms of the global economic crisis has sparked wide‐ranging debate in Europe and other Western countries, however, the research of economic resilience in China especially on Chinese old industrial cities and RBCs was still very limited.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, urban economic approaches adopting cities' delineation composed of an aggregation of localities, are restrained by the poverty of urban data to build economic resilience indicators [28,90]. Others argue, that functional criterion is much more important when distinguishing regions, particularly considering employment rate, even if the data acquisition is more complicated [95]. In doing so, Faggian [95] proposed the so called "local labor systems" that are based on the commuting between residence and workplaces and often cross administrative boundaries.…”
Section: Regional Resilience Discoursementioning
confidence: 99%